The Existence of Tourism Resources in the Coastal Area of Pantai Indah Bosowa, Makassar City - Ayu Andira; Hasriyanti H; Maddatuang M (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Tourism is  a  sector  that  is  currently  developing  and  has  even  become  a  global  phenomenon.  Indonesia's marine  and  coastal  areas  have  the  highest  biodiversity  in  the  world.  The  coastal  area  of  Makassar  city  is  located  in  the  Tanjung  Bunga  Metro  Area,  Tamalate  District,  Makassar  City,  South  Sulawesi.  This  research  is  a  type  of  qualitative  research  with  the  sampling  technique  used  is  purposive  sampling  with  data  collection  techniques  used,  namely  1)  observation  techniques,  2)  interview  techniques,  3)  documentation  techniques. The  results show that the coastal  area  of  Indah  Bosowa  has  qualified  potential  both  in  terms  of  beauty  and  others,  the  beautiful  beach  of  Bosowa  is  considered  a  very  new  beach  considering  the  year  it  was  built  around  2020  so  that  tourism  management  needs  to  be  done.